2001
DOI: 10.1021/jm0101085
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Agents. 211. Fluorinated 2-Phenyl-4-quinolone Derivatives as Antimitotic Antitumor Agents

Abstract: Fluorinated 2-phenyl-4-quinolone derivatives were synthesized and evaluated in National Cancer Institute's 60 human tumor cell line in vitro screen. From the results, the ketone moiety plays an essential role in activity. Among the compounds tested, 2'-fluoro-6-pyrrol-2-phenyl-4-quinolone (13) exhibited the most potent cytotoxic activities (log GI(50) < -8.00) against renal and melanoma tumor cell lines. Compound 13 was also a potent inhibitor of tubulin polymerization (IC(50) = 0.46 microM) and of radiolabele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 13 publications
0
73
0
Order By: Relevance
“…has undergone an activating phosphorylation (on Thr 161 ) by CAK, that inhibitory phosphorylation (on Thr 14 and Tyr 15 ) has been removed by active Cdc25C phosphatase, that Cdc2 associates with cyclin B1, and that complex translocates to the nucleus (24). In this study, CHM-1 arrested the growth of cancer cells at the G 2 -M phase and then induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 58%
“…has undergone an activating phosphorylation (on Thr 161 ) by CAK, that inhibitory phosphorylation (on Thr 14 and Tyr 15 ) has been removed by active Cdc25C phosphatase, that Cdc2 associates with cyclin B1, and that complex translocates to the nucleus (24). In this study, CHM-1 arrested the growth of cancer cells at the G 2 -M phase and then induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 58%
“…The 2-arylquinolin-4-ones and their quinoline derivatives continue to receive considerable attention in chemistry because of their wide range of pharmacological applications [1][2][3][4]. The 2-arylquinolin-4(1H)-one derivatives, for example, are known to exhibit antibacterial [1] and antitumour properties [2].…”
Section: Introductionmentioning
confidence: 99%
“…The 2-phenyl-4-quinolones and related compounds, a series of synthetic quinolone derivatives, were found to inhibit tubulin polymerization and disrupt microtubule organization, and they act as antimitotic agents (17)(18)(19)(20)(21). It was reported that the 2-phenylpyrroloquinolin-4-ones have antitumor activity in vitro and in vivo (22).…”
mentioning
confidence: 99%